Preliminary Studies on The Germination Behaviour of Adhatoda vasica Seeds: an Important Shrub for Regreening of Sub-Himalayan Wastelands - Bahuguna, V. K.; Sood, O. P.; Rawat, M. S. S. (Indian Forester, 1987)
No abstract